Composição e estrutura de grupos florísticos em fragmento de floresta secundária - Rocha, Karen Janones da (2015)
The general objective of this study was to characterize a secondary fragment of semideciduous forest located in Tapurah-MT, as its structure and forest composition, verify the formation of floristic groups and also explore possible relationships with the environment. Was applied the fixed area method with five rectangular clusters of 10 x 250 m, they were measured and allocated to five subunits of 10 x 50 m each. In each sample subunit was considered all tree and shrub species with diameter at breast height (DBH) greater than or equal to 10 cm. The floristic composition was analyzed for the number of families, genera and plant species found in the survey of the tree component and sampling sufficiency of floristic survey was tested by bootstrap procedure. The floristic similarity between plots was obtained through the Jaccard index and the diversity of species in the sample subunits was measured by the Shannon Index (H') and equability index of Pielou (J'). The characterization of the horizontal structure of vegetation was made from the phytosociological parameters and the structure diameter by Spiegel procedure. The presence of floristic groups was verified by the association method of species and the number of groups was established by Kendall concordance coefficient, where for each floristic group was analyzed horizontal structure, the pattern of spatial distribution of species by Payandeh index and the diameter distribution of individuals by Spiegel procedure. The construction of the matrix of the soil variables was performed in a preliminary analysis to identify variables similar to the sample subunits, which showed no influence were dropped. The correlation between the data of vegetation and environmental data was performed by Canonical Correlation Analysis, which allowed confirm that soil nutrients influence the presence of the species and the Canonical Redundancy Analysis to evaluate which environmental variables had the greatest influence on the individuals. In the studied fragment was observed high variability floristic and structural, which can be explained by historical local disturbance that this fragment was in the past. In general, the vegetation corresponds to young secondary forests and presents a stable and self-regenerative community, besides preserving the original structure characteristics. Through cluster analysis it was found that the ecological self characteristics of the species as well as the average DBH of each species were mainly responsible for the association and similarity between the groups. We also observed that despite the disturbances in the environment that emphasize the saturation of forest site, the fragment is recovering. The soil variables heterogeneity related influence the floristic-structural behavior of the secondary fragment of semideciduous forest. Being, the species of the families: Fabaceae, Lauraceae, Moraceae and Vochysiaceae the most influential for the present study. Highlighting the Qualea paraensis Ducke about its ecological significance and adaptability to the environment.